Hubungan antara Metode Pembelajaran Diskusi dan Keaktifan Belajar Siswa Mata Pelajaran IPS - Noldin Jerry Tumbel; Deisye Supit; Citra Anjeli Suoth (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
The purpose of this study was to determine the relationship between discussion learning methods and student learning activities in social studies subjects. The researcher adapted the questionnaire from Khasanah (2021) and Diendrich (1992) and then distributed it to 125 students of class VIII A, B, C, and D at Adventist Junior High School Airmadidi Unklab to find out whether the discussion learning method was often used for student learning activities in social studies subjects. This research is a quantitative research that is descriptive and correlative, used to answer the formulation of the problem. The purpose of this study was to determine the relationship between discussion learning methods and student learning activities in social studies subjects. The researcher adapted the questionnaire from Khasanah (2021) and Diendrich (1992) and then distributed it to 125 students of class VIII A, B, C, and D at Adventist Junior High School Airmadidi Unklab to find out whether the discussion learning method was often used for student learning activities in social studies subjects. This research is a quantitative research that is descriptive and correlative, used to answer the formulation of the problem.